Lewis & Clark The Great American Expedition - Producer, Joe Loesch; Topics Entertainment, Reston, WA ([S.l.] : cd, 2003)
With Thomas Jefferson's purchase of the vast Louisiana Territory, the U.S. President was one step closer to realizing his dream of a nation spanning the oceans. The next step e=was exploration of this new geographical possession. Thus began the unbelievable 4-year odyssey chronicled on 8 audio compact discs in Lewis & Clark: The Great American Expedition.
8 CDs
Topics Entertainment - audio collection
W
Not rated.
8 compact discs
Keywords: Clark, William, -- 1770-1838.; Lewis, Meriwether, -- 1774-1809.